2015
DOI: 10.1002/jcp.24900
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Decreases Hydrogen Peroxide-Induced Damage to NG108-15 Cells via Upregulation of Nrf2

Abstract: Baicalein is a flavonoid inhibitor of 12-lipoxygenase. Here, we investigated its effect on hydrogen peroxide-induced damage to NG108-15 cells. Hydrogen peroxide activated the mitochondrial apoptotic pathway, decreased Nrf2 expression, increased reactive oxygen species (ROS) levels, reduced viability, and increased cell death after 2-24 h treatment of NG108-15 cells. Co-treatment with hydrogen peroxide and baicalein completely suppressed the activation of mitochondrial apoptotic pathway by upregulating Nrf2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…In the present study, we found that baicalein increased Nrf2 protein expression and decreased Keap1 in a concentration-and time-dependent manner in C6 cells. These results are consistent with those of previous studies (42)(43)(44), and were associated with the induction of HO-1 and TrxR1. However, the inhibition of HO-1 function using ZnPP significantly weakened the inhibitory effects of baicalein on H 2 O 2 -induced MMP loss, growth inhibition, and apoptosis by blocking PARP cleavage, XIAP inhibition, and γH2A.X phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that baicalein increased Nrf2 protein expression and decreased Keap1 in a concentration-and time-dependent manner in C6 cells. These results are consistent with those of previous studies (42)(43)(44), and were associated with the induction of HO-1 and TrxR1. However, the inhibition of HO-1 function using ZnPP significantly weakened the inhibitory effects of baicalein on H 2 O 2 -induced MMP loss, growth inhibition, and apoptosis by blocking PARP cleavage, XIAP inhibition, and γH2A.X phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found that their expression levels were inhibited in 3-AT-treated adipocytes. First, our results agree with a recent study that found that H 2 O 2 lowers NRF2 expression [ 46 ]. Moreover, the inflammatory response present in adipocytes treated with 3-AT could also explain the reduced NRF2 expression because it has been widely demonstrated that Nrf2 and NF-κB behave antagonistically [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…The chemical structure and properties of baicalein are shown in Figure 1. Emerging evidence has demonstrated that baicalein exerts multiple pharmacological effects including anti-inflammatory [17], antioxidant [18], and antiviral [19] properties, as well as protection against cardiovascular illness [20]. In the past decade, there has been great progress in exploring the target mechanisms and signaling pathways of baicalein’s anti-cancer potential.…”
Section: The Property and Antitumor Effect Of Baicaleinmentioning
confidence: 99%